Incidence and risk factors related to anxiety of children and adolescents before elective surgery - Maryam Ahmadipour; Hossein Sattari; Mehdi Ahmadi Nejad (PAGEPress Publications, 2022)
The goal of this study was to evelaute the preoperative anxiety in children and adolescents and to identify some of the risk factors associated with the incidence of anxiety in 9-18 years old group. Children and adolescents 9-18 years old hospitalized the night before elective surgeries were analyzed in terms of incidence and severity of anxiety using the State-Trait Anxiety Inventory (STAI) measure. Of the 164 patients, 111 (67.6%) suffered from preoperative anxiety. The incidence of anxiety in children aged 9-12 was 2.88 times the anxiety of those aged 12-18 (OR = 2.88) (1.65, 5.98). Moreover, the incidence of anxiety in only children was 0.65 times that of children with siblings (OR = 0.78) (0.11,2.93) , and in patients with a history of hospitalization, the incidence was 1.85 times the stress in children without hospitalization history (OR = 1.85)(1.31,3.99); finally, the incidence of anxiety in children of higher socioeconomic status was lower compared with those of lower socioeconomic status (OR = 0.13) (0.08,0.35). Having close frend or family in the healthcare staff decreased the prevalence (OR = 0.64 (0.23,1.79) and severity of anxiety (47.02 ± 5.48 vs. 54.18 ± 7.18) (P-value = 0.001). There was no relationship between gender and the incidence of anxiety (OR = 1). Incidence of preoperative anexiety in foriner was1.72 times of persion patients (OR=1.72) (0.99,4.25). The severity of anxiety was lower in boys (46.22 ± 6.68) compared with girls (52.55 ± 7.52) (P-value = 0.002) and lower in patients of medium-to-high socioeconomic status (43.64 ± 5.45) compared with those with lower socioeconomic status (49.66 ± 6.49) (P-value = 0.003). There was no relationship between being an only child and severity of anxiety (P-value = 0.54) (48.31 ± 5.05 vs. 48.12 ± 6.81). However, anxiety was more severe in patients with a history of hospitalization (50.55 ± 4.64) (49.2 ± 6.23) (P-value = 0.09). Severity of anexiety was not dependent to nationality of patients(P-value = 0.6) .Taken together, our data suggest that various methods should be used to reduce anxiety and associated complications, regarding the high prevalence of anxiety in mentioned groups of children and adolescents.